Analisis Pengaruh Kualitas Layanan dalam Kepuasan Konsumen Terhadap Shopee (Studi Kasus di Kecamatan Lamongan Kabupaten Lamongan) - Dimas Wahyu Agustian; Muhammad Syarif (Management Department of Economics and Business Of Trunojoyo Madura University, 2026)
In today's technological developments, business and trade activities are also known as e-commerce or online purchasing. With e-commerce, it is easy for consumers to buy goods, providing E-commerce requires services like security features and discounts. This study's objective is to ascertain how service quality affects Shopee customer happiness. Purposive sampling, which selects a sample of 67 respondents based on predetermined criteria, is the methodology employed in this study. Using the IBM SPSS 29 application, a Simple Regression Test is used for data analysis. The study's findings demonstrate a link between the dependent variable, customer satisfaction, and the independent variable, service quality. The findings indicate that a probability of Sig 0.00 was attained for the service quality variable (X) t test results. The computed t value is, and the Sig value is 0.00 0.05 in the t table 7.233 known to be 1.997 (see t table). 7.233 1.997, it is determined that Ho1 is rejected and Ha1 is accepted. This indicates that Shopee e-commerce customer happiness is positively and significantly impacted by service quality.